Relative stability of ordered phases in bcc Cu-Al-Zn - Lanzini, Fernando Gabriel (2011)
The relative stability of the short range ordered and different long range ordered structures in body centered cubic CuAlZn is studied by means of the Cluster Variation Method in the Irregular Tetrahedron approximation (IT-CVM). The energetic parameters (constant pair interchange energies for first and second neighbor pairs) used in our calculations have been extracted from experimental orderdisorder transition temperatures. It is shown that the use of constant pair interchange energies allows accurate reproduction of the experimental transition temperatures in the binary subsystems CuAl and CuZn. Several isothermal sections of the ternary system at temperatures between 600 and 900 K have been calculated. The two-phase field for compositions around Cu3Al in the ternary system was determined: It was found that such region extends to around 15 at.% Zn in the pseudo-binary Cu 0.760.5xAl0.240.5xZnx.